Antenna Selection and Power Allocation in Massive MIMO - Selvam, Paranche Damodaran; Vishvaksenan, Kuttathati Srinivasan (Společnost pro radioelektronické inženýrství, 2019)
This paper explores the massive multiple-input multiple-output (Ma-MIMO) communication system possessing large number of antennas at the basestation (BS) serving multiple user terminal (UT) in single cell configuration. Due the large number of antennas at the BS, the RF chains used is also increasing with the increase in the total power consumption of the system such as circuit power consumption, filter, mixer and digital to analog converter power consumption. The main aim of this paper is to reduce the transmit power consumption with the proposed antenna selection and power allocation approach. Initially, the equal power is allocated to users to find the optimal number of antenna selection. Then for the number of antennas selected the optimal power allocation is derived to users. An algorithm is proposed to iteratively find the antenna selection and power allocation. The simulation is done to evaluate the average data rate and to find the optimal transmit power of the system.
Keywords: Massive MIMO; antenna selection; power allocation